Community structure of fishes and macroinvertebrates and their relationships with selected habitat characteristics in tributaries of upper Sarawak Kiri River, Sarawak - Angie, Sapis (Universiti Malaysia Sarawak, (UNIMAS), 2014)
A study of the relationships among community structure of fish and macroinvertebrate with vegetation cover types and water quality was conducted at six tributaries of upper Sarawak Kiri River: Sawah River, Kan River, Menying River, Abang River, Temong River and Semadang River with twelve sampling from October 2011 to September 2012. Fish and macroinvertebrate sampling were carried out using electrofishing technique while water quality sampling was conducted in-situ and ex-situ. Stream and habitat assessment was also recorded at each station. ArcGIS 9.2 Desktop GIS software, with the aid of digital base map was used to delineate catchment boundaries of each watershed. GIS tools were used to calculate the percentage and area of each river catchment and to estimate the area of each vegetation cover types. Vegetation cover types in each tributary catchment were categorised into six types which are open areas, intensive farming system, traditional agroforestry and rubber farming, young secondary forests, old secondary forests and primary forests. Pearson’s correlation analysis, Analysis of Variance (ANOVA), Principal Component Analysis (PCA), Detrended Correspondence Analysis (DCA), and multiple (Stepwise method) linear regression were conducted to study the community structure of fish and macroinvertebrate and their relationships with selected habitat characteristics in the six tributaries of upper Sarawak Kiri River. The objectives of this thesis were to determine species diversity and abundance of fish and macroinvertebrate at six tributaries of upper Sarawak Kiri River, to determine the the relationships between community structure of fish and macroinvertebrate, stream physicochemical parameters, vegetation cover and water quality and to determine the most important parameters influencing community structure of the fauna. The water quality parameters (except dissolved oxygen, biochemical oxygen demand, ammonium-nitrogen, and nitrate) were significantly (p < 0.05) different among the sampling stations. A total of 2,708 fishes belonging to 35 species, 21 genera, and 11 families are recorded in the study area. Fish belonging to the family Cyprinidae, Mastacembelidae, Hemiramphidae and Channidae are widely distributed among all the six sampling stations. High diversity and abundance of fish, especially the intolerant species, Tor douronensis, Gastromyzon spp., and Leiocassiss micropogon, are recorded in the forested rivers and catchments of Semadang River, Sawah River, Kan River, Temong River and Abang River. A total of 64 taxa from 41 families belonging to 15 order of macroinvertebrate were recorded in this study. The study areas are dominated by Ephemeroptera and Decapoda as well as cosmopolitan species such as Isolapotamon consobrinum from the family Potamidae belonging to Decapoda (Brachyra), Macrobrachium pilimanus from the family Palaemonidae belonging to Decapoda (Caridae), and Chlorogomphus sp. from the family Chlorogomphidae belonging to Odonata. Results of statistical analyses show that the assemblages of fish and macroinvertebrate are highly influenced by the width of the rivers. In addition, different vegetation cover variables within the river catchments also influenced the assemblages of these aquatic fauna in the river.